Effect Of E-Service Quality And Online Review on Guest Satisfaction at Virtual Hotel Operator in The City Of Semarang - Tuwuh Adhistyo; Wenefrida Ardhian Ayu Hardiani; Mukhamad Kholil Aswan (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to find out how the destination business is to place he is always in the minds of consumers so that perceptions are different from competitors. This strategy to get achieve customer satisfaction in the long term, therefore it is needed PIB approach that is strung through the creative economy to achieve communicating uniqueness of the destination. This research was conducted in Kartikajaya Village in Kendal, Central Java. Source The data of this research are primary and secondary data. This research was obtained through interviews directly and filling out the questionnaire using the google form to strengthen the result data study. The principle of data collection is to reveal the variables to be studied. Method data collection through direct observation to the field, interviews, questionnaires. This research is an action research panel of previous researchers where a potential study model was found the attractiveness of the creative economy has strength in tourism development, and then followed by the importance of building a positioning strategy with a PIB approach (Positioning-Image-Branding) where 3 related concepts are united with the creative economy in marketing strategy. Indonesia has designated Kendal as a Special Economic Zone (SEZ). With With this status, investors are increasingly interested in developing their business in the Kendal SEZ. By because it will certainly have an impact on the development of the creative economy in the surrounding area Kendal, especially Kartika Jaya Village, has opportunities for economic development that will can contribute to the country's foreign exchange through its tourism programs. Data source Government, community organizations, local communities, and tourists. Research output, a document that reviews the potential of the destination, describes a list of attractions (for mapping potential), competitive analysis, including situation analysis. The document is the basis to start brand development. Furthermore, the imaging (image) of tourist destinations is agreed upon This in turn strengthens its brand positioning among the local community and the market. Process branding involves all individuals/institutions in the tourism industry to identify themselves with the brand to be established, so that local stakeholders become guard of the brand development process.